IL-2 Restores T-Cell Dysfunction Induced by Persistent Mycobacterium tuberculosis Antigen Stimulation - Liu, Xun; Li, Fei; Niu, Hongxia; Ma, Lan; Chen, Jianzhu; Zhang, Ying; Peng, Liang; Gan, Chao; Ma, Xingming; Zhu, Bingdong (Frontiers in Immunology, 2019)
Tuberculosis (TB) is a chronic disease mainly caused by Mycobacterium tuberculosis (M. tuberculosis). The function of T cells usually decreased and even exhausted in severe TB such as multiple drug resistant TB (MDR-TB), which might lead to the failure of treatment in return. The mechanism of T cell dysfunction in TB is still not clear. In this study we set up a mouse model of T cell dysfunction by persistent M. tuberculosis antigen stimulation and investigated the therapeutic role of interleukin 2 (IL-2) in it. C57BL/6 mice were primed with Mycobacterium bovis Bacillus Calmette-Guérin (BCG) and boosted repeatedly with a combination of M. tuberculosis fusion proteins Mtb10.4-HspX (MH) plus ESAT6-Ag85B-MPT64<190-198>-Mtb8.4-Rv2626c (LT70) or MH plus ESAT6 and CFP10 with adjuvant of N, N′-dimethyl-N, N′-dioctadecylammonium bromide (DDA) plus polyinosinic-polycytidylic acid (Poly I:C). Following persistent antigen stimulation, the mice were treated with IL-2 and the therapeutic effects were analyzed. The results showed that compared with the mice that received transient antigen stimulation (boost twice), persistent antigen stimulation (boost more than 10 times) resulted in decrease of antigen specific IFN-γ and IL-2 production, reduction of memory CD8+ T cells, over-expression of immune checkpoint programmed cell death protein 1 (PD-1), and impaired the protective immunity against bacterial challenge. Treating the T cell functionally exhausted mice with IL-2 restored antigen-specific T cell responses and protective efficacy. In conclusion, persistent stimulation with M. tuberculosis antigens induced T cell dysfunction, which could be restored by complement of IL-2.